Silicon-carbon negative electrode material and preparation method thereof, secondary battery and electric equipment

By designing a layered porous mesh structure with carbon-covered silicon particles and carbon fibers in the negative electrode material of lithium-ion secondary batteries, the problems of low capacity and volume expansion of the negative electrode material are solved, and high conductivity and excellent cycling and rate performance are achieved.

CN119812264AActive Publication Date: 2025-04-11SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411984141.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The negative electrode material capacity of lithium-ion secondary batteries is low, and the volume expansion of the silicon negative electrode during charging and discharging is severe, resulting in the collapse of the electrode material structure and deterioration of electrochemical performance.

Method used

A silicon carbon negative electrode material is designed to form a layered porous mesh structure by coating silicon particles through carbon fibers, and the Raman spectral parameters and Poisson's ratio of the material are reasonably controlled to meet the specific relationship.

Benefits of technology

It effectively alleviates the volume expansion of the material, improves the conductivity, and significantly improves the circulation and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222428700000101
    Figure BDA0005222428700000101
  • Figure BDA0005222428700000111
    Figure BDA0005222428700000111
  • Figure BDA0005222428700000121
    Figure BDA0005222428700000121
Patent Text Reader

Abstract

The invention provides a silicon-carbon negative electrode material and a preparation method thereof, a secondary battery and electric equipment. Comprising carbon fibers and carbon-coated silicon particles located in the carbon fibers, the carbon fibers are mutually lapped to form a layered porous net structure, and the silicon-carbon negative electrode material meets the following relational expression: 4lt; a * b * clt; 15); wherein a cm <-1 > is the full width at half maximum of a G peak of the silicon-carbon negative electrode material in a Raman spectrum; b is the ratio of the D peak intensity to the G peak intensity in the Raman spectrum of the silicon-carbon negative electrode material; c is the Poisson ratio of the silicon-carbon negative electrode material. According to the invention, the structure of the silicon-carbon negative electrode is designed, silicon is subjected to carbon coating and then is embedded into the carbon fibers, and the carbon fibers are further in lap joint to form a layered porous net-shaped film structure; meanwhile, the parameters of the silicon-carbon negative electrode material are reasonably controlled to meet a specific relational expression, so that the volume expansion of the material can be effectively relieved, the conductivity of the material is improved, and the cycle performance and the rate capability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of negative electrode materials, in particular to a silicon-carbon negative electrode material, a secondary battery and an electrical device. Background Art

[0002] Lithium-ion secondary batteries are the main energy storage devices in today's new energy field. As the main commercial negative electrode, the low capacity of carbon materials has limited the development of lithium-ion secondary batteries. The theoretical specific capacity of silicon negative electrodes is the highest, but its volume expansion during charging and discharging is as high as 300%, and the intrinsic conductivity of silicon is low; the huge volume effect during charging and discharging will cause the electrode material structure to collapse, and even peel off from the current collector, causing electrochemical performance degradation; the electrode structure of the traditional coating method contains a large proportion of inert components, such as metal current collectors, conductive agents, binders, etc., which increases the weight of the battery while also increasing the internal resistance.

[0003] Therefore, it is necessary to modify and rationally design the negative electrode materials of secondary batteries in order to improve the comprehensive performance of secondary batteries, such as conductivity, cycle performance and rate performance. Summary of the invention

[0004] An object of the present application is to provide a secondary battery having excellent cycle performance and rate performance.

[0005] To achieve the above-mentioned purpose, in a first aspect of the present application, a silicon-carbon negative electrode material is provided, comprising carbon fibers and carbon-coated silicon particles located inside the carbon fibers, wherein the carbon fibers overlap each other to form a layered porous network structure, and the silicon-carbon negative electrode material satisfies the following relationship:

[0006] 4 <a×b×c<15;

[0007] Among them, a cm -1 is the half-height width of the G peak of the silicon-carbon negative electrode material in the Raman spectrum;

[0008] b is the ratio of the D peak intensity to the G peak intensity in the Raman spectrum of the silicon-carbon negative electrode material;

[0009] c is the Poisson's ratio of the silicon-carbon negative electrode material.

[0010] As an embodiment of the present application, the peak position of the D peak of the silicon-carbon negative electrode material in the Raman spectrum is 1300 cm -1 ~1380cm -1 .

[0011] As an embodiment of the present application, the peak position of the G peak of the silicon-carbon negative electrode material in the Raman spectrum is 1520 cm -1 ~1590cm -1 .

[0012] As an embodiment of the present application, the silicon-carbon negative electrode material satisfies: 10cm -1 ≤a≤25cm -1 .

[0013] As an implementation scheme of the present application, the silicon-carbon negative electrode material satisfies: 0.6≤b≤1.5.

[0014] As an implementation scheme of the present application, the silicon-carbon negative electrode material satisfies: 0<c≤0.5.

[0015] As an implementation scheme of the present application, based on the silicon-carbon negative electrode material, the weight proportion of silicon is 2 to 15%.

[0016] As an implementation scheme of the present application, based on the silicon-carbon negative electrode material, the weight proportion of the carbon fiber is 35 to 78%.

[0017] As an embodiment of the present application, based on the silicon-carbon negative electrode material, the weight proportion of the carbon coating layer in the carbon-coated silicon particles is 20 to 50%.

[0018] The second aspect of the present application further provides a method for preparing the silicon-carbon negative electrode material described in the first aspect of the present application, comprising the following steps:

[0019] After the silicon source and the first carbon source are uniformly mixed in a solvent, the second carbon source is added and mixed uniformly to form a colloidal precursor solution, and the colloidal precursor solution is subjected to electrostatic spinning to form a film and carbonized to obtain the silicon-carbon negative electrode material;

[0020] The first carbon source is a polar carbon-containing macromolecule, which forms a carbon coating layer in the carbon-coated silicon particles; and the second carbon source is a precursor polymer for forming carbon fibers.

[0021] As an embodiment of the present application, the first carbon source includes at least one of epoxy resin, cellulose, and polyvinylidene fluoride.

[0022] As an embodiment of the present application, the second carbon source includes at least one of polyvinyl pyrrolidone, polyvinyl alcohol, and polyacrylonitrile.

[0023] According to a third aspect of the present application, a secondary battery is provided, comprising a positive electrode plate, an electrolyte, a separator and a negative electrode plate, wherein the negative electrode plate comprises a negative electrode collector and a negative electrode active material layer comprising the silicon-carbon negative electrode material described in the first aspect of the present application and arranged on at least one surface of the negative electrode collector.

[0024] In a fourth aspect of the present application, an electrical device is further provided, wherein the electrical device comprises the secondary battery described in the third aspect of the present application.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present application designs the structure of the silicon-carbon negative electrode, carbon-coates the silicon, and then embeds it into the carbon fiber, and the carbon fiber is further overlapped to form a layered thin film structure with a porous mesh; at the same time, the parameters of the silicon-carbon negative electrode material (such as the ratio of the D peak intensity to the G peak intensity in the Raman spectrum, the half-width of the G peak, and the Poisson's ratio) are reasonably controlled to satisfy specific relationships, which can effectively alleviate the volume expansion of the material, improve the conductivity of the material, and improve the cycle performance and rate performance. DETAILED DESCRIPTION

[0027] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. The technical scheme in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of this application.

[0028] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0029] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0030] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0031] The first aspect of the present application provides a silicon-carbon negative electrode material, the silicon-carbon negative electrode material comprising carbon fibers and carbon-coated silicon particles located inside the carbon fibers, the carbon fibers overlap each other to form a layered porous network structure, and the silicon-carbon negative electrode material satisfies the following relationship:

[0032] 4 <a×b×c<15;

[0033] Among them, a cm -1 is the half-height width of the G peak of the silicon-carbon negative electrode material in the Raman spectrum;

[0034] b is the ratio of the D peak intensity to the G peak intensity in the Raman spectrum of the silicon-carbon negative electrode material;

[0035] c is the Poisson's ratio of the silicon-carbon negative electrode material.

[0036] The present application designs the structure of the silicon-carbon negative electrode, carbon-coates the silicon, and then embeds it into the carbon fiber, and the carbon fiber is further overlapped to form a layered thin film structure with a porous mesh; at the same time, the parameters of the silicon-carbon negative electrode material (such as the ratio of the D peak intensity to the G peak intensity in the Raman spectrum, the half-width of the G peak, and the Poisson's ratio) are reasonably controlled to satisfy specific relationships, which can effectively alleviate the volume expansion of the material, improve the conductivity of the material, and improve the cycle performance and rate performance.

[0037] It should be noted that the silicon-carbon negative electrode material of the present application is in the form of a fiber film, in which the carbon fiber matrix can be used as a part of the negative electrode active material and can also be used as a current collector. Therefore, the silicon-carbon negative electrode material of the present application can be pressed into sheets and used as a negative electrode sheet without being loaded onto the surface of the metal current collector.

[0038] In some embodiments, the D peak of the silicon-carbon negative electrode material in the Raman spectrum is at 1300 cm -1 ~1380cm -1 .

[0039] In some embodiments, the peak position of the G peak of the silicon-carbon negative electrode material in the Raman spectrum is 1520 cm -1 ~1590cm -1 .

[0040] In some embodiments, the silicon-carbon negative electrode material satisfies: 10 cm -1 ≤a≤25cm -1 In this application, a (unit is cm -1 ) represents the half-width of the G peak in the Raman spectrum of the silicon-carbon negative electrode material, that is, the difference between the two wavelengths corresponding to half of the G peak intensity. The half-width a is related to the defect concentration and disorder of the hard carbon material in the silicon-carbon negative electrode material. Specifically: the defect concentration of the hard carbon material will affect the hindrance of lithium ion migration in its internal solid phase, thereby affecting the kinetic properties of the hard carbon material; at the same time, the disorder of the hard carbon material reflects the capacity of the silicon-carbon negative electrode material to a certain extent. When the value of the G peak intensity a of the silicon-carbon negative electrode material is within the above range, the defect concentration and disorder of the carbon material therein are moderate, and the lithium-ion secondary battery containing the silicon-carbon negative electrode material as the negative electrode active material has better first-cycle coulomb efficiency and cycle rate performance. Exemplarily, the value of a can be 10.5cm -1 、11.0cm -1、14.5cm -1 、16.2cm -1 、18.3cm -1 、25.0cm -1 Any value or a range between any two values, more preferably 12cm -1 ≤a≤20cm -1 .

[0041] In some embodiments, the silicon-carbon negative electrode material satisfies: 0.6≤b≤1.5, and more preferably 0.8≤b≤1.2. Exemplarily, the value of b can be any one of 0.75, 0.99, 1.05, 1.31, 1.39, 1.50 or a range between any two values. b=ID / IG represents the defect concentration of the silicon-carbon negative electrode material, which is the ratio of the D peak intensity (expressed by ID) to the G peak intensity (expressed by IG) in the Raman spectrum of the silicon-carbon negative electrode material. When the value of b is within the above-mentioned appropriate range, the silicon-carbon negative electrode material has a suitable defect concentration and moderate active reaction sites, which can well balance the contradiction between the side reactions and lithium storage capacity of lithium-ion secondary batteries during the charging and discharging process, and the battery has a first-cycle coulomb efficiency and a long cycle life.

[0042] In some embodiments, the silicon-carbon negative electrode material satisfies: 0<c≤0.5, preferably 0.4≤c≤0.49. c is the Poisson's ratio of the silicon-carbon negative electrode material, which is the elastic coefficient of material deformation and is positively correlated with the bending effect of the material. The silicon-carbon negative electrode material within this Poisson's ratio range has sufficient flexibility, and during the charging and discharging process of the lithium-ion secondary battery, the specific distribution between the carbon fiber and the carbon-coated silicon particles in the silicon-carbon negative electrode material can effectively buffer the volume change of silicon during the charging and discharging process. The combination of carbon fiber and carbon-coated silicon particles also greatly improves the conductivity of the silicon-carbon negative electrode material, thereby greatly improving the cycle performance and rate performance of the lithium-ion secondary battery. Exemplarily, the value of c can be any one of 0.30, 0.35, 0.39, 0.45, 0.48, 0.49 or a range value between any two values.

[0043] In some embodiments, based on the silicon-carbon negative electrode material, the weight proportion of silicon is 2-15%, and illustratively, it can be any value among 2%, 10%, 15%, or a range value between any two values. Silicon has a higher ability to embed and de-embed lithium ions, so it can improve the energy storage capacity of lithium batteries, but its volume will expand during the process of lithium ion de-embed, which will affect the cycle life and rate performance of lithium-ion secondary batteries. The appropriate silicon content in the negative electrode material can make the prepared lithium-ion secondary battery have both high first-cycle coulomb efficiency and rate performance.

[0044] In some embodiments, based on the silicon-carbon negative electrode material, the weight proportion of the carbon coating layer in the carbon-coated silicon particles is 20-50%. Exemplarily, it can be any value among 20%, 30%, 50% or a range value between any two values.

[0045] In some embodiments, based on the silicon-carbon negative electrode material, the weight proportion of the carbon fiber is 35-78%, and specifically, it can be any one of 35%, 40%, 60%, 78% or a range value between any two values.

[0046] The ratio of the two carbon materials and silicon in the silicon-carbon negative electrode material will affect the structure of the silicon-carbon negative electrode material, especially the coating integrity of the carbon material, and thus affect the cycle performance. The parameters of the silicon-carbon negative electrode material can be adjusted to control the usage ratio of each component within an appropriate range, thereby ensuring its excellent electrochemical performance.

[0047] The second aspect of the present application provides a method for preparing the silicon-carbon negative electrode material described in the first aspect of the present application, comprising the following steps:

[0048] After the silicon source and the first carbon source are evenly mixed in a solvent, the second carbon source is added and mixed evenly to form a colloidal precursor solution. The colloidal precursor solution is subjected to electrostatic spinning to form a film and carbonization to obtain the silicon-carbon negative electrode material; wherein the first carbon source is a polar carbon-containing macromolecule, which forms a carbon coating layer in the carbon-coated silicon particles; and the second carbon source is a precursor polymer for forming carbon fibers.

[0049] In some embodiments, the first carbon source comprises at least one of epoxy resin, cellulose, and polyvinylidene fluoride. The first carbon source forms a carbon coating layer in the carbon-coated silicon particles.

[0050] In some embodiments, the second carbon source includes at least one of polyvinyl pyrrolidone, polyvinyl alcohol, and polyacrylonitrile. The second carbon source can form a carbon fiber matrix.

[0051] In some embodiments, the silicon source includes at least one of silicate, elemental silicon, and silicon dioxide; preferably silicate, which has better compatibility with the first carbon source and the second carbon source, and the structural distribution of the prepared silicon-carbon negative electrode material is more uniform. The silicate includes at least one of sodium silicate, lithium silicate, potassium silicate, and ammonium silicate.

[0052] In some embodiments, the solvent includes at least one of water, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, and ethylene carbonate. Conventional electrospinning solvents in the art can be used in the present application.

[0053] In some embodiments, the mass concentration of the silicon source in the colloidal precursor solution is 1% to 20%.

[0054] In some embodiments, the electrospinning parameters are: pushing speed 0.1-0.5 mL / h, spinning distance 10-20 cm, spinning voltage 10-25 kV, collector speed 150-300 rpm.

[0055] In some embodiments, the carbonization process parameters are specifically: a heating rate of 2 to 10° C. / min; a carbonization temperature of 800 to 1100° C.; and a carbonization time of 1 to 4 hours.

[0056] The third aspect of the present application provides a secondary battery, which includes the silicon-carbon negative electrode material described in the first aspect of the present application. Specifically: the secondary battery includes a positive electrode plate, an electrolyte, an isolation membrane and a negative electrode formed by the silicon-carbon negative electrode material described in the first aspect of the present application.

[0057] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer contains a negative electrode active material.

[0058] The type of positive electrode current collector is not specifically limited and can be selected according to actual needs.

[0059] The positive electrode current collector may include but is not limited to metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, etc.; carbon materials such as carbon cloth and carbon paper; composite materials formed by polymers and metal layers. In some embodiments, the positive electrode current collector preferably uses aluminum foil.

[0060] In the present application, the type of positive electrode active material is not limited and can be selected according to actual needs. For example, the positive electrode active material can be lithium iron phosphate, lithium iron manganese phosphate, or a ternary positive electrode material. The positive electrode active material may also contain doping elements and / or coating elements. There are no special requirements for the doping elements and / or coating elements, as long as they can make the positive electrode active material more stable.

[0061] In addition, the positive electrode active material layer further includes at least one of a conductive agent, a binder, and a thickener.

[0062] Commonly used battery conductive agents, binders and thickeners in the art can be used in this application.

[0063] In some embodiments, the conductive agent includes but is not limited to at least one of graphite, carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphene.

[0064] In some embodiments, the binder includes but is not limited to at least one of styrene-butadiene rubber, polyacrylic acid, polyacrylonitrile, polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene copolymer, and vinylidene fluoride-hexafluoropropylene copolymer.

[0065] In some embodiments, the thickener includes but is not limited to at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.

[0066] In some embodiments, the type of solvent used to form the positive electrode slurry and / or the negative electrode slurry is not limited, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the negative electrode active material, the conductive agent, the binder, and the dispersant.

[0067] In the secondary battery described in the present application, the type of the separator is not particularly limited and can be selected according to actual needs. The separator can be a polypropylene film, a polyethylene film, a polyvinylidene fluoride, a spandex film, an aramid film, or a multilayer composite film modified by a coating.

[0068] In the secondary battery described in the present application, the type of electrolyte is not particularly limited and can be selected according to actual needs.

[0069] In some embodiments, the preparation of a secondary battery includes: stacking the positive electrode sheet, the isolation membrane, and the negative electrode in order, so that the isolation membrane is between the positive and negative electrodes to play an isolating role, and then winding it into a square bare battery, loading it into a battery casing, and then baking it at 65 to 95°C to remove water, injecting electrolyte, sealing, and obtaining a secondary battery after standing, hot and cold pressing, formation, clamping, capacity division and other processes.

[0070] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package, and the material of the soft package may be plastic, such as one or more of polypropylene, polybutylene terephthalate, polybutylene succinate, etc. There is no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0071] The fourth aspect of the present application provides an electrical device comprising the secondary battery described in the third aspect. The electrical device may be an application device such as a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, and an electric tool. The vehicle may be a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle, or an extended-range vehicle; the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft; the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy; the electric tool may include a metal cutting electric tool, a grinding electric tool, an assembly electric tool, and an electric tool for railways, such as an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an impact drill, a concrete vibrator, and an electric planer. The embodiments of the present application do not impose any special restrictions on the above-mentioned devices.

[0072] The following are specific embodiments of the present application, and the technical scheme of the present application is further described in conjunction with the embodiments, but the present application is not limited to these embodiments. The reagents, methods and equipment used in the present application, unless otherwise specified, are conventional reagents, methods and equipment in the art.

[0073] Example 1

[0074] A silicon-carbon negative electrode material is provided, and a method for preparing the silicon-carbon negative electrode material specifically comprises the following steps:

[0075] Weigh the raw materials according to the ratio in Table 1, add epoxy resin (i.e., the aforementioned first carbon source) and sodium silicate to 66.67wt% ethanol aqueous solution, mix well, add polyvinyl pyrrolidone (i.e., the aforementioned second carbon source), stir for 30min under ultrasonication, stir at room temperature for 12h to form a uniform colloidal precursor solution (the mass concentration of sodium silicate in the colloidal precursor solution is 1.70wt%);

[0076] The prepared colloidal precursor solution was injected into a syringe, and the pushing speed was set to 0.25 mL / h, the spinning distance was 15 cm, the spinning voltage was 15 kV, and the collector speed was 200 rpm for electrospinning. The obtained product was collected and placed in a drying oven at 50°C for 12 h, and then placed in an argon atmosphere tubular furnace, heated to 1000°C at 5°C / min, kept at a constant temperature for 2 h, and cooled to room temperature (25±5°C) to obtain the silicon-carbon negative electrode material. The characterization of the relevant parameters of the obtained silicon-carbon negative electrode material is shown in Table 1.

[0077] Examples 2 to 13, Comparative Examples 1 to 2

[0078] A series of silicon-carbon negative electrode materials are provided, which are prepared by referring to the method of Example 1. Silicon-carbon negative electrode materials with different parameters are obtained by changing the types and usage ratios of the raw materials in Example 1, the parameters of the electrospinning (including the spinning distance, etc.), the carbonization temperature and time, etc. The parameters of the obtained silicon-carbon negative electrode materials are detailed in Table 1.

[0079] Comparative Example 3

[0080] A silicon-carbon negative electrode material is provided, which is prepared by referring to the method of Example 1. The difference from Example 1 is that the epoxy resin (first carbon source) is replaced by an equal mass of polyvinyl pyrrolidone (second carbon source), and the electrospinning parameters and carbonization temperature are adjusted to ensure that the relationship between the parameters satisfies the calculated value of a×b×c and is the same as that in Example 1.

[0081] Comparative Example 4

[0082] A silicon-carbon negative electrode material is provided, which is prepared by referring to the method of Example 1. The difference from Example 1 is that the second carbon source polyvinyl pyrrolidone is replaced by an epoxy resin (first carbon source) of equal mass, that is, the second carbon source polyvinyl pyrrolidone is not added, and the electrospinning parameters and carbonization temperature are adjusted to ensure that the relationship between the parameters satisfies the calculated value of a×b×c, which is the same as that in Example 1.

[0083] Comparative Example 5

[0084] A silicon-carbon negative electrode material is provided, which is prepared by referring to the method of comparative example 3. The difference from comparative example 3 is that the electrospinning parameters and the carbonization temperature are adjusted to ensure that the relationship between the parameters a×b×c<4.

[0085] Comparative Example 6

[0086] A silicon-carbon negative electrode material is provided, which is prepared by referring to the method of comparative example 4. The difference from comparative example 3 is that the electrospinning parameters and the carbonization temperature are adjusted to ensure that the relationship between the parameters a×b×c>15.

[0087] About the parameters of silicon-carbon negative electrode materials:

[0088] 1) In the present application, the proportion of each component in the silicon-carbon negative electrode material product can be calculated by the thermogravimetric differential thermal (TG-DTA) method. The specific calculation method is: the silicon-carbon negative electrode material is tested under an argon atmosphere for a thermogravimetric differential thermal curve, and then the content of the silicon material and the carbon material is first calculated according to the weight loss curve, and then the content of the carbon fiber matrix and the coated carbon layer is further calculated by the ratio of the two carbon sources. The specific results are shown in Table 1;

[0089] 2) In the present application, the Raman spectrum test conditions of the silicon-carbon negative electrode material are as follows: the material is placed under a Raman spectrometer and tested at a constant temperature of 25°C. The ratio of the D peak intensity to the G peak intensity of the material Raman spectrum is b: b = I D / I G , where I D Indicates the D peak intensity of the material's Raman spectrum. The D peak has a wavelength of 1350cm in the Raman spectrum. -1 Nearby (1300cm is selected in this application -1 -1380cm -1 range); I G Indicates the G peak intensity of the material's Raman spectrum. The wavelength of the G peak in the Raman spectrum is 1580cm -1 Nearby (1520cm is selected in this application -1 -1590cm -1 within the scope);

[0090] 3) Poisson's ratio c: obtained by referring to the method in the standard "GB / t3354-2014" and tested using a tensile testing machine. The tensile rate was 50 mm / min and the test temperature was room temperature (i.e., 25±5°C). The test results are detailed in Table 1.

[0091] Table 1 Parameters of silicon-carbon negative electrode materials

[0092]

[0093] The silicon-carbon negative electrode materials provided in the above embodiments and comparative examples were prepared into batteries and subjected to electrochemical performance tests. The specific preparation process includes the following steps:

[0094] Preparation of positive electrode

[0095] The positive electrode active material lithium iron phosphate, conductive agent acetylene black, dispersant PVP and binder polyvinylidene fluoride were dispersed in NMP in a mass ratio of 96:1.2:1:1.8 to prepare a slurry, which was then coated on both sides of aluminum foil. After baking, rolling and cutting, the positive electrode sheet (surface density 0.22g / 1540.25mm 2 );

[0096] Preparation of negative electrode

[0097] The silicon-carbon negative electrode active materials prepared in the above examples and comparative examples were compacted to obtain negative electrode sheets (surface density 0.135 g / 1540.25 mm 2 );

[0098] Preparation of electrolyte

[0099] EC and DMC were mixed in a volume ratio of 1:1, and then lithium hexafluorophosphate was added in a glove box to prepare an electrolyte with a concentration of 1 mol / L;

[0100] Battery Assembly

[0101] The prepared positive electrode sheet, polyethylene separator, and negative electrode sheet are stacked in order so that the separator is between the positive and negative electrode sheets, and a bare battery cell is obtained after winding. The bare battery cell is placed in an outer packaging shell, and after vacuum drying, an electrolyte is injected, and the battery is allowed to stand, formed, shaped, and divided to obtain a secondary battery.

[0102] The performance of the secondary batteries obtained in the above examples and comparative examples was tested, and the specific test items, test methods and results are as follows:

[0103] 1. Cycle performance test:

[0104] Place the secondary battery in a charge and discharge test cabinet, at a constant temperature of 25°C, with a charge rate of 1C and a discharge rate of 1C, and perform a cycle test within a voltage range of 2.5 to 3.65V; when the capacity drops to 80% of the initial capacity, stop the test and record the first-cycle discharge capacity and the number of cycles;

[0105] Take the negative electrode sheet of the secondary battery before and after cycling, place the negative electrode sheet under a resistance meter to measure the resistance value of the sheet, and record the initial sheet resistance (ρ0) and the sheet resistance after cycling (ρ t ), and calculate the resistance change rate of the negative electrode plate = (ρ t )-ρ0) / ρ0*100%;

[0106] 2. Rate performance test:

[0107] Place the secondary battery in a charge and discharge test cabinet at a constant temperature of 25°C, with a charge rate of 1C, and a discharge rate of 1C and 5C. After 5 cycles in the voltage range of 2.5 to 3.65V, record the capacity at different rates, which are recorded as C1 and C5 respectively. Calculate the capacity retention rate at 5C rate = C5 / C1*100%;

[0108] 3. Bending stiffness: Take a pole piece made of the material, place the pole piece under a bending test machine, and use a two-point bending test method to measure the bending stiffness of the pole piece according to DIN 53121 or ISO 5628 standards.

[0109] Table 2 Performance test results of negative electrode sheets and batteries prepared in Examples and Comparative Examples

[0110]

[0111]

[0112] From the above results we can see that:

[0113] From the above embodiments and comparative examples, by designing the structure of the silicon-carbon negative electrode, silicon is carbon-coated and then embedded in the carbon fiber, and the carbon fiber is further overlapped to form a layered thin film structure with a porous mesh; at the same time, the parameters of the silicon-carbon negative electrode material (such as the ratio of the D peak intensity to the G peak intensity in the Raman spectrum, the half-width of the G peak, and the Poisson's ratio) are reasonably controlled to satisfy a specific relationship, which can effectively alleviate the volume expansion of the material, improve the conductivity of the material, and improve the cycle performance and rate performance.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material comprises carbon fibers and carbon-coated silicon particles located inside the carbon fibers, the carbon fibers overlap each other to form a layered porous mesh structure, and the silicon-carbon negative electrode material satisfies the following relationship: 4 <a×b×c<15; a cm -1 is the half-height width of the G peak of the silicon-carbon negative electrode material in the Raman spectrum; b is the ratio of the D peak intensity to the G peak intensity in the Raman spectrum of the silicon-carbon negative electrode material; c is the Poisson's ratio of the silicon-carbon negative electrode material.

2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The silicon-carbon negative electrode material satisfies at least one of the following characteristics: (1) In the Raman spectrum, the peak position of the D peak of the silicon-carbon negative electrode material is 1300 cm -1 ~1380cm -1 ; (2) In the Raman spectrum, the peak position of the G peak of the silicon-carbon negative electrode material is 1520 cm -1 ~1590cm -1 .

3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The value of a satisfies: 10cm -1 ≤a≤25cm -1 .

4. The silicon-carbon negative electrode material according to claim 1, characterized in that: The value of b satisfies: 0.6≤b≤1.

5.

5. The silicon-carbon negative electrode material according to claim 1, characterized in that: The value of c satisfies: 0<c≤0.

5.

6. The silicon-carbon negative electrode material according to any one of claims 1 to 5, characterized in that: The silicon-carbon negative electrode material satisfies at least one of the following characteristics: (1) Based on the silicon-carbon negative electrode material, the weight proportion of silicon is 2 to 15%; (2) Based on the silicon-carbon negative electrode material, the weight proportion of the carbon fiber is 35-78%; (3) Based on the silicon-carbon negative electrode material, the weight proportion of the carbon coating layer in the carbon-coated silicon particles is 20 to 50%.

7. The method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 6, characterized in that: The steps include: After the silicon source and the first carbon source are uniformly mixed in a solvent, the second carbon source is added and mixed uniformly to form a colloidal precursor solution, and the colloidal precursor solution is subjected to electrostatic spinning to form a film and carbonized to obtain the silicon-carbon negative electrode material; The first carbon source is a polar carbon-containing macromolecule, which forms a carbon coating layer in the carbon-coated silicon particles; and the second carbon source is a precursor polymer for forming carbon fibers.

8. The method for preparing the silicon-carbon negative electrode material according to claim 7, characterized in that: Satisfies at least one of the following characteristics: (1) The first carbon source includes at least one of epoxy resin, cellulose, and polyvinylidene fluoride; (2) The second carbon source includes at least one of polyvinyl pyrrolidone, polyvinyl alcohol and polyacrylonitrile.

9. A secondary battery comprising a positive electrode sheet, an electrolyte, a separator and a negative electrode sheet, characterized in that: The negative electrode plate comprises the silicon-carbon negative electrode material according to any one of claims 1 to 6.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Negative electrode material and preparation method thereof, electrochemical device and electronic device

    CN115443559A

  • Silicon-carbon negative electrode material and preparation method thereof, lithium ion battery and electric device

    CN116632212A

  • Negative pole piece, lithium ion battery and electronic device

    CN117038855A

  • Preparation method and application of multilayer carbon-coated silicon-carbon composite material

    CN118712370A

  • Anode active material for lithium secondary battery and method for preparing same

    US20160013481A1